Influence of sex and habitat on the size and shape of anal and dorsal fins of the blackstripe topminnow Fundulus notatus. Issue 1 (27th November 2014) - Welsh, D. P.; Fuller, R. C.
<x xml:space="preserve">Abstract</x> The size and shape of the anal and dorsal fin in the blackstripe topminnow Fundulus notatus from lake and stream habitats across multiple ages and sexes were examined. Differences in the size and shape of anal and dorsal fins were sex‐specific and not related to habitat differences. Males have longer and more pointed anal fins and longer, larger and more pointed dorsal fins than females. These sex differences occur predominantly in the older age class. The angle (i.e. pointedness) of the dorsal and anal fins is tightly correlated suggesting that fins follow a similar growth trajectory as individuals become sexually mature.